2018
DOI: 10.1002/pros.23513
|View full text |Cite
|
Sign up to set email alerts
|

The impact of intraductal carcinoma of the prostate on the site and timing of recurrence and cancer‐specific survival

Abstract: In our cohort, presence of IDC-P was an independent factor for distant metastasis at initial CR, but did not have a significant impact on time to CR. Furthermore, metastatic patients showed statistically reduced cancer-specific mortality when treated with radiotherapy. This reduction in cancer-specific mortality was also identified in patients with IDC-P. Future large scale validation studies should take into account the presence of IDC-P and confirm its impact on disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Our group reported that IDC‐P is an adverse prognostic factor for patients with high‐risk or metastatic PCa patients . A recent paper pointed out the higher tendency of distant metastasis rather than local recurrence in IDC‐P‐positive patients at the first clinical detection of recurrence and that it influenced cancer‐specific survival . Molecular evidence also supports the association of a TMPRESS2‐ERG genomic change and the heterozygosity of RB1 and TP53 in patients with IDC‐P .…”
Section: Introductionsupporting
confidence: 62%
“…Our group reported that IDC‐P is an adverse prognostic factor for patients with high‐risk or metastatic PCa patients . A recent paper pointed out the higher tendency of distant metastasis rather than local recurrence in IDC‐P‐positive patients at the first clinical detection of recurrence and that it influenced cancer‐specific survival . Molecular evidence also supports the association of a TMPRESS2‐ERG genomic change and the heterozygosity of RB1 and TP53 in patients with IDC‐P .…”
Section: Introductionsupporting
confidence: 62%
“…Whether IDC-P is a harbinger of aggressive, advanced disease or a precursor lesion is important for risk stratification among PCa patients and for determining aggressiveness of subsequent therapy. For example, recent data have demonstrated a benefit of adjuvant radiation therapy in patients with IDC-P [57]; while definitive therapy is certainly prudent, such additional adjuvant therapy would likely be overtreatment after RP in cases with iIDC-P. Additionally, we demonstrate that iIDC-P may have a distinct molecular pathogenesis from conventional PCa, and one that may lend itself to targeted therapies, should these cancers be identified in a progressed state. In this context, targeted sequencing of could be potentially beneficial, although identifying advanced PCa that may have originated as iIDC-P remains a challenge.…”
Section: Discussionmentioning
confidence: 61%
“…Table 1 shows the characteristics of the included studies. [11][12][13][14][15][16][17][18][19][20][21][22][23] These studies were published between 2010 and 2019. A total of 4179 patients from 6 countries including Portland, Canada, Japan, America, China and Norway were enrolled.…”
Section: Study Characteristicsmentioning
confidence: 99%